2020
DOI: 10.1111/bjh.16659
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among lymphocyte subsets, cytokines, and the pulmonary inflammation index in coronavirus (COVID‐19) infected patients

Abstract: We explored the relationships between lymphocyte subsets, cytokines, pulmonary inflammation index (PII) and disease evolution in patients with (corona virus disease 2019) COVID-19. A total of 123 patients with COVID-19 were divided into mild and severe groups. Lymphocyte subsets and cytokines were detected on the first day of hospital admission and lung computed tomography results were quantified by PII. Difference analysis and correlation analysis were performed on the two groups. A total of 102 mild and 21 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
293
4
7

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(328 citation statements)
references
References 10 publications
15
293
4
7
Order By: Relevance
“…Some authors have also reported a role for IL-6 and IL-10 in monitoring COVID-19 patients. In particular, significantly higher levels of IL-6 and IL-10 have been identified in severe COVID-19 patients than in the milder forms, thus suggesting that these cytokines can be used to predict the transition from mild to severe infection [47].…”
Section: Chloroquine and Hydroxychloroquinementioning
confidence: 99%
“…Some authors have also reported a role for IL-6 and IL-10 in monitoring COVID-19 patients. In particular, significantly higher levels of IL-6 and IL-10 have been identified in severe COVID-19 patients than in the milder forms, thus suggesting that these cytokines can be used to predict the transition from mild to severe infection [47].…”
Section: Chloroquine and Hydroxychloroquinementioning
confidence: 99%
“…Many of the transcriptomic profiling studies of COVID-19 have been conducted using peripheral blood, often revealing the upregulation of chemokines and cytokines having a direct association with the severe patient condition with SARS-CoV-2 and SARS-CoV (36,37). Expression of CXCL8 (IL-8) is an attractant for neutrophils and associated with SARS-CoV-2 infection (26).…”
Section: After Cellular Detection Of Viral Entry Into a Host Cell Inmentioning
confidence: 99%
“…The variations of immune cells levels are inconsistent in different reports. Most of our included studies found signi cant lower levels of immune cells (CD8 + T, CD4 + T, CD3 + T, B and NK cells) in severe cases compared with mild cases [2,8,12]. Only two studies reported no signi cant decrease in CD8 + T cell level [3,16], while one study reported higher levels of B cell [11] in severe cases.…”
Section: Discussionmentioning
confidence: 89%